Design of an Ejector Working in Combined Ejector – Vapor Compressor Refrigeration Cycle - Nguyen, Trung Kien; Le, Chi Hiep (JST: Engineering And Technology For Sustainable Development, 2021)
In this paper, a calculation program is developed to design ejector working in a combined ejector – vapor compression refrigeration cycle. R134a is selected as the refrigerant for the ejector sub-cycle, and R410A is selected for the compressor sub-cycle. The effect of operating conditions and cooling capacity are examined. The results show that the area ratio increases with the increasing of generator temperature and intercooler temperature; and decreases with the increasing of condenser temperature and evaporator temperature. When the generator temperature, condenser temperature, intercooler temperature and evaporator temperature are 80°C, 34°C, 15°C, 0°C respectively, the area ratio is 8.55 and independent with cooling capacity. The design equations of significant dimensions based on operating conditions and cooling capacity are also introduced. The results show that R134a ejector which is designed for simple ejector cycle is not suitable for combined cycle.